Use of Neural Networks in Picture Recognition (Eurasian Research Bulletin, 2023)
Currently, theoretical research and practical applications of artificial neural networks and parallel processing of problems are rapidly developing. Neural networks allow solving a large number of practical problems that have no analytical description and are given only by experimental data. The subtlety of algorithms in the synthesis of neural networks is the explanation of decision making. Many researchers are engaged in solving this problem